A monetary general equilibrium theory for an international economy - Meinich, Per (Oslo, Universitetsforlaget, 1971)
The present work is concerned with a monetary general-equilibrium theory of international trade which traditionally, was divided into monetary theory and international trade.
Bibliographical footnotes.
asm: 21/01/19
Loans
Keywords: Foreign exchange